Seizure after IDDS implantation – unrecognized intracranial hypertension associated with intracranial metastases - Yangyang Li; Chunmei Wu; Zehao Liu; Qing Zhong (Medicine, 2026)
Rationale: The external intrathecal drug delivery system (IDDS) provides targeted analgesia and serves as an effective therapy for refractory cancer pain. Its known complications include post-dural puncture headache, device malfunction, granuloma formation, and others. Seizures induced by occult intracranial hypertension following IDDS implantation have rarely been reported. This case report describes a cancer-pain patient who developed seizures after IDDS implantation. Patient concerns: A 66-year-old female with metastatic rectal cancer suffered from refractory lumbosacral and lower-extremity cancer pain and received external IDDS implantation for pain relief. Seizure-like symptoms occurred 19 hours after surgery. Although intracranial metastatic lesions were present preoperatively, routine evaluation revealed no obvious clinical manifestations of intracranial hypertension. Diagnoses: Secondary epilepsy was considered likely to be induced by marked intracranial-pressure fluctuations associated with jet-like cerebrospinal fluid outflow during intraoperative puncture. Emergency cranial CT revealed multiple intracranial metastatic nodules with peritumoral cerebral edema and scattered intracranial air. Several potential contributing factors, including direct tumor-related epileptogenesis, opioid neurotoxicity, chemotherapy-associated leukoencephalopathy, and acute stroke, were relatively less probable in this case. Interventions: Intrathecal morphine infusion was suspended immediately. Intravenous diazepam and mannitol were administered to reduce intracranial pressure, phenobarbital sodium and sodium valproate were used to control convulsions. Oral levetiracetam was given for long-term seizure prophylaxis. After seizure control, IDDS therapy was restarted under close monitoring with a reduced basal infusion rate. Outcomes: The patient regained consciousness after emergency management and had no further seizure episodes. Satisfactory analgesia was achieved with intrathecal therapy. Due to progressive primary malignancy, the patient’s family opted for voluntary discharge on postoperative day 8. The patient died of cardiac arrest 3 days after discharge, with no seizure recurrence during that period. Lessons: Unrecognized preoperative intracranial hypertension in patients with intracranial metastases significantly increases the risk of severe neurological complications after IDDS implantation. Reliance solely on the classic triad of intracranial hypertension is insufficient for preoperative screening. Pre-operative cranial imaging evaluation is strongly recommended for high-risk patients. Intraoperative cerebrospinal fluid loss should be strictly controlled to prevent abrupt changes in intracranial pressure. Clinicians should raise vigilance toward such life-threatening complications.